Predicting Future Cash Flows by Earnings, Cash Flow from Operation and Accruals - Paisarn, Wilaiporn; Butakhiao, Pattaraporn; Chancharat, Surachai; Chancharat, Nongnit (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2019)
The purpose of this study is to examine the ability of earnings, cash flow from operation and accruals (by two traditional measures of cash flows namely net earnings plus depreciation and amortization expense, and working capital from operation) in predicting future cash flows by using Farshadfar, Ng, and Brimble (2008); Takhtaei and Karimi (2013). This study used panel data from Thomson Reuters Datastream. The sample includes 160 listed companies in the Stock Exchange of Thailand during the period 2005-2016 (1,920 sample firms). The study applied the ordinary least square, both within-sample and out-of-sample to test the hypothesis. The results indicated that net earnings, cash flow from operation and accruals have predictability of the future cash flow at the significant level 0.01. These findings are consistent with Financial Accounting Standards Board (FASB) claim based on earnings in preference on cash flows in predicting future cash flows. Furthermore, the comparison results revealed that net earnings plus depreciation and amortization expense have the better predictive ability of future cash flow, rather than net earnings and cash flow from operation, and working capital from operation, respectively.